The Effect of Tourist Attraction, Social Media, and Price Perceptions on the Decision to Visit in Bogor - Sella Maulidini; Jammaludin Khalid (Indonesian Journal of Business Analytics, 2023)
This study aims to examine the influence of tourist attraction, social media, and price perceptions on visiting decisions at Cimory Dairyland Bogor. This study used a survey-based quantitative research design using a purposive sample of 170 respondents. This study uses primary data, or data collected directly from respondents, which includes their perceptions of aspects of tourist attraction, social media, and price perceptions. According to research findings, tourist attractiveness in Cimory Dairyland is not significantly influenced by visiting decisions, but the perceived price has a positive and significant impact. At Cimory Dairyland Bogor, service standards also have a significant influence on visiting decisions. Finally, the combined findings show that the decision to visit Cimory Dairyland Bogor is strongly influenced by tourist attractiveness, social media, and price perceptions.